(untitled) (Archaeologia Adriatica, 2017)
In the past fifteen years we have substantially improved our knowledge of the seafaring expeditions in the Mediterranean, based either on the indirect evidence of the navigation or on what we know about the earliest such ventures. This paper presents an overview of what is known about the earliest navigation in the Mediterranean and considers the origin of the first such ventures in the Adriatic as a specific part of the Mediterranean. It focuses on the problem of the navigation between the Italic and Croatian coasts, tackling the possibility of such maritime expeditions based on the distribution of the obsidian from the Aeolian Islands. It also ponders on the practical aspects of the use of sailing vessels in the Late Neolithic.